Information Transmission Availability in WDM Networks - Plėštys, R.; Šiurkus, A. (Elektronika ir Elektrotechnika, 2006)
This paper deals with the system availability estimation schemes in WDM (Wavelength Division Multiplexing) optical networks and it provides for each network topology analysis of the availability. The methodology to calculate the reliability of the optical network logical connections is introduced here. Possibilities of interferences in the connection have been calculated while assessing the amount of the reserved ways and the amount of elements in the network in every logical channel. We consider single or multiple link protection scenarios. Availability models and formulas are followed by some numerical examples that allow us to estimate availability and compare data for the different network topologies. Ill. 8, bibl. 5. (in English; summaries in English, Russian and Lithuanian).